Pengaruh Live Streaming , Flash Sale , dan Cashback Terhadap Perilaku Impulse Buying pada Pengguna E-Commerce Shopee di Surabaya - Awwaliya Dhiyaus Syamsiyah; Lia Nirawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
E-commerce is one of the newest trends in online purchasing that customers experience as a result of digital marketing. In September 2023, Shopee surpassed all other e-commerce platforms in Indonesia in terms of popularity. A number of Shopee promotional features, including live streaming, flash sales and cashback, can stimulate impulse purchases. The aim of this research is to determine the simultaneous and partial influence of live streaming, flash sales and cashback on Shopee e-commerce impulse buying behavior. An associative methodology combined with a quantitative approach was used in this research. The sampling strategy is the use of tactical purposive sampling combined with non-probability sampling. The questionnaire contains 100 responses aged between 18 and 40 years which were distributed via Google Forms as part of the data collection method, are residents of Surabaya and have made several purchases at Shopee. A multiple linear regression approach was then used to evaluate the data, and F and t tests were used to assess the hypothesis. The SPSS 29 test findings in this research show that positively and significantly live streaming, flash sales and cashback all have a big impact on impulse buying behavior at the same time or simultaneously. Meanwhile, partially live streaming (X1) contributed 54.1%, flash sales (X2) contributed 40.2%, and cashback (X3) contributed 71.3%, had a positive and significant effect on impulse buying behavior (Y). for Shopee e-commerce users in Surabaya.